Motivasi Beriman Katolik Bagi Katekumen Di Paroki Katedral Santa Maria Palangka Raya - Kara Agustri; Silvester Adinuhgra; Paulina Maria Ekasari Wahyuningrum (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
This study aims to describe the motivations of the Catholic faithful for catechumens at the Santa Maria Cathedral Parish of Palangka Raya. This research is based on the researcher's interest in the reality that the catechumens of the Palangka Raya cathedral parish come from various religions. This fact inspired researchers to find out more deeply what motivated them to become Catholics. This research uses a qualitative approach with descriptive methods. This research was conducted on May 25 – June 10, 2023. The research data was obtained using the interview method which was carried out together with 8 catechumens, 1 priest, 3 catechists or accompanying pastoral officers for catechumens. The data obtained was analyzed using the